Mindfulness-based randomized controlled trials led to brain structural changes: an anatomical likelihood meta-analysis - Siew, Savannah Kiah Hui (2024)
Mindfulness has become increasingly popular and the practice presents in many different forms. Research has been growing extensively with benefits shown across various outcomes. However, there is a lack of consensus over the efficacy of randomized controlled mindfulness interventions, both traditional and mind-body formats. This study aimed to investigate the structural brain changes in mindfulness-based interventions through a meta-analysis. Scopus, PubMed, Web of Science, and PsycINFO were searched up to April 2023. 11 studies (n = 581) assessing whole-brain voxel-based grey matter or cortical thickness changes after a mindfulness RCT were included. Anatomical likelihood estimation was used to carry out voxel-based meta-analysis with leave-one-out sensitivity analysis and behavioural analysis as follow-ups. One significant cluster (p < 0.001, Z = 4.76, cluster size = 632 mm3) emerged in the right insula and precentral gyrus region (MNI = 48, 10, 4) for structural volume increases in intervention group compared to controls. Behavioural analysis revealed that the cluster was associated with mental processes of attention and somesthesis (pain). Mindfulness interventions have the ability to affect neural plasticity in areas associated with better pain modulation and increased sustained attention. This further cements the long-term benefits and neuropsychological basis of mindfulness-based interventions.